CURRENT STATUS OF RESEARCH ON THE FEATURES OF EPIDEMIOLOGY AND DIAGNOSIS OF OBESITY IN CHILDREN AND ADOLESCENTS (literature review) (International Journal of Scientific Pediatrics, 2022)
Under the significant global influence of environmental obesity and due to access to food, non-traditional, overweight and obesity among children and adolescents has become a serious problem in the developed world, followed by developing countries. The incidence of pathology is progressively increasing, doubling every three decades and affecting the negative health of the population to the same extent as traditional global problems, since they are hunger and infectious diseases, obesity is called the modern non-communicable epidemic. Pathology is the fifth leading risk of death worldwide and contributes significantly to the occurrence and development of complications that lead to world-wide mortality, including diabetes, heart disease and some forms of cancer. Overweight and obesity were estimated to be causative factors for 3.4 million deaths worldwide in 2010, and it has been suggested that the growing trend towards obesity could significantly reduce life expectancy. Data from several studies show that the incidence of obesity in developing countries is increasing. At present, income countries, small and middle children face a double burden of nutrition problems, on the one hand they continue to struggle with malnutrition, and on the other hand, it has to face the rapid growth of non-communicable pathologies such as obesity and overweight.
Keywords: obesity in adolescent children, epidemiology, obesity risk factors, heredity